Design of Control Systems in State Space and Solving Pole-Placement Problem with Four different Methods - B. Hamid, Abdelrahim (Gezira Journal of Engineering and Applied Sciences; Vol 8 No 2 (2013), 2013)
This paper  presenting a design  method commonly called the pole-placement or  pole-assignment  technique.  Assumed  that all state variables are  measurable  and available  for feedback. It will be shown  that   if    the  system   considered  is  completely   state controllable, then poles  of  the closed-loop system may be placed at any desired  locations  by  means of  state  feedback  through an appropriate  state    feedback   gain   matrix.   The  present  design technique begins with  a determination of  the desired closed-loop poles based on the transient-response and/or frequency-response requirements. The beginning with presenting the basic materials on pole- placement in  regulator  systems.  Then  the  main problem solved with three different  methods,  followed  by  MAT LAB solution. Finally, the  criteria  of  each method and the comparison between them discussed.